2013
DOI: 10.1016/j.ahj.2013.04.018
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity cardiac troponin T in prediction and diagnosis of myocardial infarction and long-term mortality after noncardiac surgery

Abstract: Background Perioperative myocardial infarction is a serious complication after non-cardiac surgery. We hypothesized that preoperative cardiac troponin T detected with a novel high-sensitivity (hs-cTnT) assay will identify patients at risk of acute myocardial infarction (AMI) and long-term mortality after major non-cardiac surgery. Methods This was a prospective cohort study within the Vitamins in Nitrous Oxide (VINO) trial (n=608). Patients had been diagnosed with or had multiple risk factors for coronary ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
137
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 151 publications
(145 citation statements)
references
References 28 publications
6
137
1
1
Order By: Relevance
“…27) Many trials have sought prognosticating factors in noncardiac surgery. 4,5,6,10,21,22,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] In these studies, poor functional capacity, recent MI and unstable angina, decompensated heart failure, significant arrhythmia, diabetes mellitus, renal insufficiency, cerebrovascular disease, advanced age, tachycardia, anemia, surgical kind, and elevated troponin-I level were determined to be independent prognostic factors after noncardiac surgery, most of which were in agreement with our study. While the results of those studies had been generated after short-term follow-up, the present study extended the follow-up period to 7 years and attempted to provide valuable data regarding longer term mortality.…”
Section: )supporting
confidence: 78%
See 4 more Smart Citations
“…27) Many trials have sought prognosticating factors in noncardiac surgery. 4,5,6,10,21,22,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] In these studies, poor functional capacity, recent MI and unstable angina, decompensated heart failure, significant arrhythmia, diabetes mellitus, renal insufficiency, cerebrovascular disease, advanced age, tachycardia, anemia, surgical kind, and elevated troponin-I level were determined to be independent prognostic factors after noncardiac surgery, most of which were in agreement with our study. While the results of those studies had been generated after short-term follow-up, the present study extended the follow-up period to 7 years and attempted to provide valuable data regarding longer term mortality.…”
Section: )supporting
confidence: 78%
“…6,15,19) The present cohort study estimated the incidence of troponin-I elevation after major noncardiac surgery, and troponin-I positivity above 0.10 ng/mL was found in 12.2% of the patients. Studies with vascular and other highrisk but elective surgery showed an incidence of postoperative troponin elevation of 10 to 45 percent.…”
Section: )mentioning
confidence: 99%
See 3 more Smart Citations